The Existence of Infinitely Many Solutions for the Nonlinear Schrödinger–Maxwell Equations - Huang, Wen-nian; Tang, X. H. (Resultate der Mathematik, 2014)
In this paper, by using variational methods and critical point theory, we shall mainly be concerned with the study of the existence of infinitely many solutions for the following nonlinear Schrödinger–Maxwell equations - ▵ u + V ( x ) u + ϕ u = f ( x , u ) , in R 3 , - ▵ ϕ = u 2 , in R 3 , where the potential V is allowed to be sign-changing, under some more assumptions on f , we get infinitely many solutions for the system.